ANALISIS DESKRIPTIF KESULITAN BELAJAR SISWA SELAMA PEMBELAJARAN JARAK JAUH KELAS XI IPA - Yunanti, Ani (Universitas PGRI Semarang, 2023)
This study aims to determine what learning difficulties are experienced by students during distance learning. This research is a descriptive quantitative study to analyze students learning difficulties during distance learning in class XI science. The sampling technique used is cluster random sampling. Research data obtained from interviews and scale. The result showed that students had moderate learning difficulties with an average of 61, 63%. Learning experienced by students if left unchecked can affect the process and student learning outcomes so that there needs to be good cooperation from students and teachers to create effective learning sctivities.Â